War as a new reality for religious minorities of Ukraine (on the example of Jehovah’s Witnesses) - Tytarenko , Vita; Fylypovych , Liudmyla (Skhid, 2024)
Using the example of the Jehovah’s Witnesses (JW) religious organization, the authors analyze the situation for representatives of religious minorities in Ukraine in connection with the Russia-Ukraine’s war. Being institutions that, even in peacetime, occupying a non-dominant position in the structure of the religious life of Ukraine, religious minorities suffer the most from the war and its consequences compared to the majority religions. The purpose of the article is to clarify the scale of resource losses (human, material, moral), the nature of the religious minorities representatives’ activities (in this case, the JW) and the possibilities of preserving and revitalizing the activities of their communities. As a result of the study, the authors came to conclusions that can be considered a certain novelty: the war accelerated the processes of civil and national identification, strengthened people in their faith, and intensified socially useful and humanitarian assistance to the needy from religious minorities. The vast majority of communities took a distinctly patriotic position, contributing in various ways to the victory of Ukraine in the war and the establishment of a stable and just peace. At the same time, the authors predict that Ukraine after the war may be threatened with a decrease in religious pluralism due to the impossibility of reviving the activities of some small religious groups, which will not be able to return to their pre-war usual life, even if the conditions of latitude and state guarantees of human rights are preserved in the religious sphere and their communities.